2019
DOI: 10.3171/2019.5.focus19278
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following postneurosurgical Acinetobacter meningitis: an institutional experience of 72 cases

Abstract: OBJECTIVEThe authors aimed to evaluate the antimicrobial susceptibility pattern of Acinetobacter isolates responsible for nosocomial meningitis/ventriculitis in the neurosurgical ICU. The authors also sought to identify the risk factors for mortality following Acinetobacter meningitis/ventriculitis.METHODSThis was a retrospective study of 72 patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
6
10
2
Order By: Relevance
“…83.3% (5/6) of the isolates of Acinetobacter baumannii were XDR bacteria in our study, while an Indian study reported that 20.8% of Acinetobacter isolates were XDR strains [34]. An obvious difference was the sensitivity to cefoperazone-sulbactam, approximately 74% of the Acinetobacter isolates were found to be sensitive to cefoperazone-sulbactam in India [34], yet the 6 Acinetobacter baumannii isolates were all resistant in our study. The data from two Chinese hospitals indicated that Acinetobacter baumannii had low sensitivity to cefoperazone-sulbactam (5.3% and 16.3%) [21,26].…”
Section: Risk Factors For Mdr Bacterial Infectionscontrasting
confidence: 52%
“…83.3% (5/6) of the isolates of Acinetobacter baumannii were XDR bacteria in our study, while an Indian study reported that 20.8% of Acinetobacter isolates were XDR strains [34]. An obvious difference was the sensitivity to cefoperazone-sulbactam, approximately 74% of the Acinetobacter isolates were found to be sensitive to cefoperazone-sulbactam in India [34], yet the 6 Acinetobacter baumannii isolates were all resistant in our study. The data from two Chinese hospitals indicated that Acinetobacter baumannii had low sensitivity to cefoperazone-sulbactam (5.3% and 16.3%) [21,26].…”
Section: Risk Factors For Mdr Bacterial Infectionscontrasting
confidence: 52%
“…Therefore, it is important to determine the risk factors affecting the outcomes of patients with bacterial CNS infections, particularly in developing countries. Previous studies predicted survival following CNS infections and suggested that age > 40 years, presence of external ventricular drainage, low CSF glucose levels, high CSF protein levels, CSF leukocyte count > 200 cells/mm 3 , ICU admission, and the presence of comorbidities were risk factors for mortality [31,38,39]. In our analysis, age > 50, comorbidity (pulmonary infection) and CSF glucose < normal value were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies predicted survival following CNS infections and suggested that age > 40 years, presence of external ventricular drainage, low CSF glucose levels, high CSF protein levels, CSF leukocyte count > 200 cells/mm 3 , ICU admission, and the presence of comorbidities were risk factors for mortality [31,38,39]. In our analysis, age > 50, comorbidity (pulmonary infection) and CSF glucose < normal value were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 52%
“…For the Gram-negative isolates, XDR strains accounted for 20.8% of the Acinetobacter in an Indian study [31], yet, 83.3% (5/6) of the Acinetobacter baumannii strains were XDR bacteria as we showed. An obvious distinction was the sensibility to cefoperazone-sulbactum, approximately 74% of the Acinetobacter isolates were found to be sensitive to it in Indian [31]. However, Acinetobacter baumannii strains were all resistant to it in our study.…”
Section: Discussionsupporting
confidence: 51%